2016
DOI: 10.3168/jds.2016-11083
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Genomic selection in a crossbred cattle population using data from the Dairy Genetics East Africa Project

Abstract: Due to the absence of accurate pedigree information, it has not been possible to implement genetic evaluations for crossbred cattle in African small-holder systems. Genomic selection techniques that do not rely on pedigree information could, therefore, be a useful alternative. The objective of this study was to examine the feasibility of using genomic selection techniques in a crossbred cattle population using data from Kenya provided by the Dairy Genetics East Africa Project. Genomic estimated breeding values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 5 publications
3
29
1
1
Order By: Relevance
“…In addition, RRM are also more advantageous compared with P305 because selec-453 tion can be efficiently performed based on points of interest throughout the lactation curve. To overcome the limitations of P305 models, some studies have used the predicted P305 from traditional BLUP random regression genetic evaluation as a phenotype for 2-step GWS (Ding et al, 2013;Brown et al, 2016). The steps involved in the 2-step GWS approach are (1) estimation of breeding value based on traditional evaluation and its deregression and (2) estimation of direct genomic value (DGV) using deregressed EBV from step 1 as a phenotype for the genomic BLUP (GBLUP); subsequently, DGV can be combined with parent average (PA) into genomic EBV (GEBV).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, RRM are also more advantageous compared with P305 because selec-453 tion can be efficiently performed based on points of interest throughout the lactation curve. To overcome the limitations of P305 models, some studies have used the predicted P305 from traditional BLUP random regression genetic evaluation as a phenotype for 2-step GWS (Ding et al, 2013;Brown et al, 2016). The steps involved in the 2-step GWS approach are (1) estimation of breeding value based on traditional evaluation and its deregression and (2) estimation of direct genomic value (DGV) using deregressed EBV from step 1 as a phenotype for the genomic BLUP (GBLUP); subsequently, DGV can be combined with parent average (PA) into genomic EBV (GEBV).…”
Section: Introductionmentioning
confidence: 99%
“…In general, these reported studies on genomic prediction in dairy and beef cattle are characterized by small reference populations (500–3,000 animals, Table 1) and most validations are undertaken in test data sets created by either random or structured sampling from all genotyped animals. A few of these reference populations are a combination of both bulls and cows (Boison et al, 2017) but most are cows (Brown et al, 2016; Silva et al, 2016). This has implications in terms of the accuracy of genomic prediction, which has tended to be lower compared to those obtained in developed countries, given the limited information of the response variable when using cow records.…”
Section: Structure Of the Reference And Validation Populationsmentioning
confidence: 99%
“…However, in some countries like Brazil in Latin America, the existence of breed associations have resulted in the establishment of some degree of data and pedigree recording and genetic evaluation (Silva et al, 2016; Boison et al, 2017), but there is still the lack of breeding structures such as AI companies, to drive breed improvement programs. Therefore in the era of genomics, most genotyping activities in developing countries are undertaken by breed organizations or associations, such as in Brazil (Carvalheiro, 2014; Silva et al, 2016), or are a result of several development projects, such as the East Africa Dairy Development Project (Brown et al, 2016), and the African Dairy Genetic Gains Cattle project (https://www.ilri.org/node/40458). Consequently, the number of genotyped animals tend to be limited; are mostly females, and this has major influence on both the size and structure of the reference and validation populations.…”
Section: Introductionmentioning
confidence: 99%
“…Such a concept was tested on a real data set of 1,013 dairy cows in Kenya, which exhibited various degrees of crossbreeding with exotic breeds ( Brown et al, 2016 ). A principal component analysis based on SNP data showed that individuals could be clustered in three groups according to the proportion of exotic breeds, with a reference and a validation data set for each group.…”
Section: Part 1: Current Contribution Of Genomic Information To Animamentioning
confidence: 99%